MEDIA VIDEO ANIMASI BERBASIS KINEMASTER PADA MATERI HIDROKARBON DI KELAS XI SMAN 1 INUMAN - Reska Ayu Anggraini; Nofri Yuhelman; Jumriana Rahayu Ningsih (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
This research on the development of kinemaster based animated video media aims to determine the feasibility of chemistry learning media on hydrocarbon materials for class XI IPA SMAN 1 Inuman. The data collection instruments used were material expert validation sheets, media expert validation sheets, linguist validation sheets and student response validation sheets. The data analysis technique used is by calculating the percentage score of the validation assessment. The results showed that the validation results met the valid categories of material experts by 91.93%, media experts by 90.00%, and linguists by 90.47%. This learning media also meets the valid category from the results of student responses with validation gains of 91.59%. Based on these results, it can be concluded that the animated video learning media is very suitable to be used as a medium for learning chemistry on hydrocarbon materials.